2014
DOI: 10.1055/s-0034-1365515
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of prophylactic clip and endoloop application for the prevention of postpolypectomy bleeding in pedunculated colonic polyps: a prospective, randomized, multicenter study

Abstract: ClinicalTrials.gov (NCT01406379).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…Several endoscopic preventive methods, such as injection of an epinephrine‐saline solution in the stalk, the use of an endoloop and clipping over the stalk, have been performed before polypectomy because of the high risk of PPB following polypectomy in cases with large pedunculated polyps. Submucosal injection of epinephrine solution into the stalk causes vasoconstriction and mechanical compression of the polyp vessels, resulting in reduced blood flow and lower incidence of PPB .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several endoscopic preventive methods, such as injection of an epinephrine‐saline solution in the stalk, the use of an endoloop and clipping over the stalk, have been performed before polypectomy because of the high risk of PPB following polypectomy in cases with large pedunculated polyps. Submucosal injection of epinephrine solution into the stalk causes vasoconstriction and mechanical compression of the polyp vessels, resulting in reduced blood flow and lower incidence of PPB .…”
Section: Discussionmentioning
confidence: 99%
“…Submucosal injection of epinephrine solution into the stalk causes vasoconstriction and mechanical compression of the polyp vessels, resulting in reduced blood flow and lower incidence of PPB . Endoloop ligation is thought to be the most effective technique in the prevention of PPB, but its use might be limited in narrowed colon lumen or over polyps with a large head size . An alternative to these techniques is to place clips on the stalk before snare polypectomy to stop blood flow in the stalk, which is the same principle as that of the endoloop placement .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyps with thick stalks may require endoscopic pretreatment with dilute adrenaline injection to reduce the risk of periprocedural bleeding 23. Application of clips or an endoloop are alternative strategies to prevent bleeding; however, placing these prior to resection may impede the resection process.…”
Section: Endoscopic Resectionmentioning
confidence: 99%
“…A few randomized studies comparing these methods have been reported [10, 11, 12, 13, 14]. Each method has its own efficacy and its own advantages in reducing the risk of PPB; however, none of these methods is totally superior to the others.…”
mentioning
confidence: 99%